2018
DOI: 10.1111/ijlh.12826
|View full text |Cite
|
Sign up to set email alerts
|

How I investigate Clonal cytogenetic abnormalities of undetermined significance

Abstract: Myelodysplastic syndromes are a group of hematopoietic stem cell diseases characterized by cytopenia(s), morphological dysplasia, and clonal hematopoiesis. In some patients, the cause of cytopenia(s) is uncertain, even after thorough clinical and laboratory evaluation. Evidence of clonal hematopoiesis has been used to support a diagnosis of myelodysplastic syndrome in this setting. In patients with cytopenia(s), the presence of clonal cytogenetic abnormalities, except for +8, del(20q) and -Y, can serve as pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…These diagnoses are challenging and also require additional hit(s) to complete a neoplastic hematopoiesis. 37 We found that TP53 and ZRSR2 mutations were associated with poor survival. All patients with these mutations died 20 months after diagnosis, although patient numbers were very small.…”
Section: Recent Data From the Us Surveillance Epidemiology And Endmentioning
confidence: 76%
See 1 more Smart Citation
“…These diagnoses are challenging and also require additional hit(s) to complete a neoplastic hematopoiesis. 37 We found that TP53 and ZRSR2 mutations were associated with poor survival. All patients with these mutations died 20 months after diagnosis, although patient numbers were very small.…”
Section: Recent Data From the Us Surveillance Epidemiology And Endmentioning
confidence: 76%
“…In this context, recent advances in NGS have detected myeloid neoplasm‐related mutations in patients who do not meet the diagnostic criteria for MDS and various terms have been adopted to describe these cases, including clonal hematopoiesis of indeterminate potential (CHIP) and clonal cytopenia of undetermined significance (CCUS). These diagnoses are challenging and also require additional hit(s) to complete a neoplastic hematopoiesis …”
Section: Discussionmentioning
confidence: 99%
“…Should del(20q) in our patient considered as the newly emerged isolated del(20q) in patients following cytotoxic therapies? The patients who acquired isolated del(20q) after cytotoxic therapy had innocuous BM finding in more than 77% of patients . Moreover, would the abnormal clone react equivalently in our patient as in the donor?…”
Section: Discussionmentioning
confidence: 87%
“…The patients who acquired isolated del(20q) after cytotoxic therapy had innocuous BM finding in more than 77% of patients. 11,12 Moreover, would the abnormal clone react equivalently in our patient as in the donor? The interplay of BM microenvironment and leukemia cells has been suggested, 13 and there is a chance that the del(20q) clone will progress to myeloid neoplasm in the BM microenvironment of someone previously diagnosed with AML harboring the same cytogenetic abnormality.…”
Section: Del(20q) Along With Other Hematological Malignancy-associatedmentioning
confidence: 96%
“…Clonal aberrations can be frequently observed in irradiated patients and healthy controls [ 15 , 24 , 29 , 30 ], as well as in aged persons [ 31 ] and hypothetically reflect a stem cell pool depletion or an outgrowth of a particular lymphocyte population due to a premalignant process in a hematopoietic stem/progenitor cell or an immunological stimulation of a lymphocyte subpopulation. The time of persistence and dynamics of circulating clones are yet to be determined.…”
Section: Discussionmentioning
confidence: 99%